An economic analysis of advances in the Kurdistan Region and the role of private banks In providing the necessary funds for these advances during (2003-2012) - Lava Aras Ibrahim; Ezzat Saber Ismail (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
This research sheds light on the Kurdistan Regional Government’s financing to some social groups within the form of lending advances. The process began in 2003 and continued until 2012. The government’s plan was lacking three profound elements. First, it put pressure on the government budget and distorted families’ plans in building their houses or small businesses. Second, as the money did not go through the commercial banks, it limited its circulation in the domestic economy. Banks can distribute risks over a large number of savers. They are able to circulate money in the economy. They are also a bridge between savers and borrowers. This was ignored by the government. Third, inequality in paying the amount spent was one of the causes of decreasing government liquidity and wasting public financial resources. Although the amount of money provided in a form of zero-interest-rate-lending has had positive impacts of the growth of several economic sectors, meanwhile has had negative effects on shortages of domestic currency and its circulation in the domestic economy.